Forgiveness in Organisation among Managers (Jurnal Pembangunan Sosial, 2013)
Managers are challenged with the daunting task of employee motivation and enhancing their efficiencies. The concept of forgiveness may help makes the task easier as forgiveness is an important factor in enhancing better working relationship and fosters motivating working environment and leads to higher morale. Therefore deriving from various literatures on philosophy and management this paper intends to conceptually discuss the role of managers in enhancing a sense of and creating a culture of forgiveness in an organization. A review of the literature on philosophy, management and operation was conducted in order to conceptually explore the role of managers in enhancing a sense of and creating a culture of forgiveness in an organization. Managers play a critical role in enhancing a sense of forgiveness in an organization. Their role focuses on creating and preparing a positive environment that are conducive for employees’ emotional readiness to forgive any acts or wrongdoings against them at the work place. In doing this, the manager also should be able to forgive as well. Furthermore managers must also develop and create a culture that enhance the sense of forgiveness in an organization by undertaking the various processes that could lead to the act of forgiveness which will bring positive results to the organization. This in turn will assist the organization to meet its goals.